Menjadi kaya dengan kedamaian fikiran - Hill, Napoleon (Siri motivosi pengurusan & kecemerlangan diri, 1999)
This book eveals the authors' latest discoveries about getting what you want--and making the most of it. Here, in simple, readable language, are the foolproof techniques for achieving the power to earn money and to enjoy genuine inner peace.